2021
DOI: 10.3390/ani11051264
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Hyaluronic Acid Administration in Dogs Following Tibial Tuberosity Advancement Surgery for Cranial Cruciate Ligament Injury

Abstract: Hyaluronic acid (HA) intraarticular injection is used in the management of osteoarthritis in veterinary medicine. However, HA oral administration is less common given the scarce currently available scientific evidence. This study was aimed at evaluating the effects of oral HA administration on synovial fluid concentrations of several selected biomarkers in dogs with cranial cruciate ligament (CCL) injury operated on using the tibial tuberosity advancement (TTA) technique. Fifty-five dogs were included in this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Random sequence generation and allocation concealment were evaluated to assess selection bias. Twelve studies were considered to produce low risk of selection bias ( Table 1 ) regarding random sequence generation and allocation concealment (as they used adequate methods to generate the allocation sequence: these studies assign subjects via computer-assisted lists ( 31 , 36 , 37 , 39 , 48 , 54 , 65 , 66 ) such as Excel or commonly available online tools, via coin toss ( 35 , 38 , 44 ) or by referring to a random number table ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Random sequence generation and allocation concealment were evaluated to assess selection bias. Twelve studies were considered to produce low risk of selection bias ( Table 1 ) regarding random sequence generation and allocation concealment (as they used adequate methods to generate the allocation sequence: these studies assign subjects via computer-assisted lists ( 31 , 36 , 37 , 39 , 48 , 54 , 65 , 66 ) such as Excel or commonly available online tools, via coin toss ( 35 , 38 , 44 ) or by referring to a random number table ( 40 ).…”
Section: Resultsmentioning
confidence: 99%
“…They were therefore considered to have a low risk of performance and detection bias ( Table 1 ). Some studies described blinding to some extent ( 37 , 65 ) or it was not possible to blind all personnel and owners to all treatments ( 31 , 32 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since OA is associated with HA degradation over time, the HA administered was, mainly, of high molecular weight (MW) and usually injected directly into the joint [33]. However, oral forms can also be used with good bioavailability and efficacy [34,35]. A study has shown that HA of high MW can be found in dogs' joints after oral administration [36].…”
Section: Introductionmentioning
confidence: 99%